Implementing QR code system on student attendance by using : mobile app / Meor Muhammad Nazrin Norazman - Norazman, Meor Muhammad Nazrin (2019)
Web-based student attendance system is a system that integrated with mobile apps and web-based system to implement the QR code technology on student attendance using mySQL as a cloud database which was developed specifically to reduce the workload and reduce time taken for lecturer to take the students attendance in class. This system using QR code function to update and scan the attendance by using mobile apps generated by web-based. Besides, the web-based features such as sent warning email to the student who below eighty percent which can alert the student that was in warning state before they got barred from the final examination for the specific registered course. Other than that, admin and lecturer also can generate QR code for new class attendance for the student to scan and take the attendance and data was stored in the cloud database. Furthermore, the mobile apps was for students, which provided the information about registered courses and percentage of attendance and also QR scanner function to scan the attendance. The development of student attendance system using QR code used the System Development Cycle (SDLC) which contains five phases in the project management. A user acceptance test and network performance test were applied for the testing phase. User acceptance test was conducted with 30 respondents, which are UiTM Arau students and lecturers by evaluating the questionnaires. Results of the questionnaires showed that most of the participant were satisfied with all categories provided. Moreover, another part of testing that was carried out is the network performance test on the network response time, and packet loss was shown a good result and acceptable. Therefore, based on features and functionality offered in this system will benefit to UiTM Arau citizens.